1989
DOI: 10.1143/jjap.28.2581
|View full text |Cite
|
Sign up to set email alerts
|

Photon-Stimulated Desorption of H+ Ions from Oxidized Si(111) Surfaces

Abstract: Photon-stimulated desorption (PSD) experiments on oxidized Si(111) surfaces were performed to study the adsorption of hydrogen at the SiO2/Si(111) interface using synchrotron radiation. H+ is found to be the only ion product desorbing in significant quantities from the oxidized surfaces at photon energies above 20 eV. PSD spectra of H+ ions, i.e., the H+ ion desorption yield as a function of photon energy, exhibit two peaks at 23 eV and 33 eV. These peaks are interpreted in terms of Si-H bond and O-H bond brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…35,36 For the ions on the solid surface, such as OH − and H + on the SiO 2 surface, the energy threshold for removing the OH − from the SiO 2 surface is about 8.5 eV, 37 and it is about 20 eV for removing the H + . 38 Therefore, the ions (OH − and H + ) are rather hard to be removed from the surfaces when the temperature is not too high.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…35,36 For the ions on the solid surface, such as OH − and H + on the SiO 2 surface, the energy threshold for removing the OH − from the SiO 2 surface is about 8.5 eV, 37 and it is about 20 eV for removing the H + . 38 Therefore, the ions (OH − and H + ) are rather hard to be removed from the surfaces when the temperature is not too high.…”
supporting
confidence: 89%
“…It was revealed that the electron transfer may be dominant in the CE between aqueous solutions and solids, as a consequence of the electron cloud overlap between the two atoms belonging to the aqueous solutions and solid surfaces. , Hence, the charge carriers in the CE between functional group modified solid surfaces and liquids have to be further identified. Fortunately, previous studies provide a method to quantify electron transfer and ion transfer between liquid and solid, in which the electrons are demonstrated to be easily emitted from the solid surfaces induced by thermionic emission. , For the ions on the solid surface, such as OH – and H + on the SiO 2 surface, the energy threshold for removing the OH – from the SiO 2 surface is about 8.5 eV, and it is about 20 eV for removing the H + . Therefore, the ions (OH – and H + ) are rather hard to be removed from the surfaces when the temperature is not too high.…”
mentioning
confidence: 99%
“…As a result, the stoichiometric value could not be obtained in the present study. 27,28 It should be pointed out here that lower C H compared with other processes is one of the features of SR-excited CVD. Figure 3 shows the relationship between C H and N/Si at T S ϭ200°C and compares this relationship with C H values obtained by other low-temperature processes.…”
Section: A Physical and Chemical Propertiesmentioning
confidence: 86%
“…8 These features have made SR one of the most useful light sources for spectroscopy at photon energies above the visible region and the for x-ray lithography. [18][19][20] In a previous work, we studied SRs feasibility as a light source in photoexcited processes and demonstrated that a silicon nitride ͑SiN͒ film can be deposited using a SiH 4 ϩN 2 gas mixture as well as SiH 4 ϩNH 30 , and it was revealed that substrate surface excitation plays a key role in the deposition mechanism. [18][19][20] In a previous work, we studied SRs feasibility as a light source in photoexcited processes and demonstrated that a silicon nitride ͑SiN͒ film can be deposited using a SiH 4 ϩN 2 gas mixture as well as SiH 4 ϩNH 30 , and it was revealed that substrate surface excitation plays a key role in the deposition mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of synchrotron radiation irradiation during processes such as chemical vapour deposition (CVD) of silicon is to remove surface adsorbates at low temperature by photonstimulated desorption (PSD) instead of thermal desorption . The detailed removal ef®ciency of irradiation has so far been explored by measuring the PSD yield of positive ions using time-of-¯ight mass spectrometry (TOF-MS) (Ueno et al, 1996) and quadrupole mass spectrometry (QMS) (Takakuwa et al, 1989). The ion detection ef®ciency of TOF-MS is much higher than that of QMS, because a microchannel plate (MCP) with a larger detection area above 25 mm diameter is available as a detector for the TOF-MS measurement.…”
Section: Introductionmentioning
confidence: 99%